From data management to actionable market insight : development of a market intelligence concept model for an industrial manufacturer organization - Lehtimäki, Marja (My University, 2020)
The operational decision-making of industrial manufacturer organizations generally utilizes the internal business information collected by the organizations. For example, organizations analyse sales and production data stored in their information systems. However, collecting market data is more challenging, as export organizations often do not have access to comprehensive country-specific data on markets, customers and competitors. The situation is particularly challenging within industrial manufacturer organizations located far from the markets and end customers. This master’s thesis uses the Design science research method to create a market intelligence concept model for a Finnish industrial manufacturer organization that supports the collection, visualization, analysis and dissemination of internal business information, macroeconomic information and external market information. The concept model takes into account the organization's strengths and weaknesses in collecting and disseminating market information. To ensure efficiency and usefulness, the concept model utilizes the organization's existing sales channel structure as well as information system infrastructure and tools. The effective integration of the concept model into the organization's operational decision-making is ensured by taking into account the compatibility of the concept with business processes and corporate culture. The literature review examines the process models of information management, data processing and information systems. The overall functionality of the concept model was evaluated during the development of the concept with Proof of Concept iterations, which provided feedback on the functionality of the model and based on which the changes were made to the model. The usefulness, suitability and effectiveness of the final concept model and the value it created for the organization were evaluated in a separate internal workshop. The results of the workshop support the usefulness of the concept. Also, practical examples of the utilization of market information in the organization's operational activities show the value of the concept and the market information it produces for the organization. However, the concept model needs to be regularly evaluated and developed based on the improvement proposals from users and new requirements set by changes in the business environment. The developed concept model can be utilized to some extent in other export organizations. However, it should be noted that the concept model as such is not usable, as organizations differ in terms of structure, processes, business environment, information system architecture, values and corporate culture.

Valmistavan teollisuuden vientiyritysten operatiivisessa päätöksenteossa hyödynnetään yleisesti yritysten keräämää sisäistä liiketoimintatietoa. Yritykset analysoivat esimerkiksi tietojärjestelmiinsä varastoitua myynti- ja tuotantodataa. Markkinatiedon kerääminen on kuitenkin haastavampaa, sillä vientiyrityksillä ei useinkaan ole käytettävissään riittävän kattavia maakohtaisia tietoja markkinoista, asiakkaista ja kilpailijoista. Erityisen haastava tilanne on teollisuuden vientiyrityksissä, jotka sijaitsevat kaukana markkinoista ja loppuasiakkaista. Tässä tutkielmassa luodaan Design science -tutkimusmenetelmän avulla eräälle suomalaiselle valmistavan teollisuuden vientiyritykselle markkinatietojärjestelmän konseptimalli, joka tukee yrityksen sisäisen liiketoimintatiedon, makrotaloustiedon ja ulkoisen markkinatiedon keräämistä, visualisointia, analysointia ja levittämistä, ja joka tukee markkinatietoon pohjautuvaa operatiivista päätöksentekoa erityisesti myynnin ja markkinoinnin näkökulmasta. Konseptimalli huomioi yrityksen organisatoriset vahvuudet ja heikkoudet markkinatiedon keräämiseen ja levittämiseen liittyen. Tehokuuden ja käytettävyyden varmistamiseksi konseptimalli hyödyntää yrityksen myyntikanavarakennetta sekä tietojärjestelmäinfrastruktuuria ja -työkaluja. Konseptimallin tehokas integroituminen osaksi yrityksen operatiivista päätöksentekoa varmistetaan huomioimalla konseptin yhteensopivuus liiketoimintaprosessien ja yrityskulttuurin kanssa. Tutkielman kirjallisuusosiossa tarkastellaan tiedonhallinnan, tiedonkäsittelyn ja liiketoiminta-järjestelmien prosessimalleja. Konseptimallin yleistä toimivuutta arvioitiin konseptin kehitysvaiheen aikana Proof of Concept -kokeiluilla, joiden avulla saatiin palautetta mallin toimivuudesta ja jonka perusteella malliin tehtiin tarvittavia muutoksia. Valmiin konseptimallin hyödyllisyyttä, sopivuutta ja tehokkuutta sekä sen luomaa arvoa yritykselle arvioitiin erillisessä workshopissa. Yrityksen sisäisen workshopin tulokset tukevat kehitetyn konseptin hyödyllisyyttä. Lisäksi useat käytännön esimerkit markkinatiedon hyödyntämisestä yrityksen operatiivisessa toiminnassa osoittavat sekä konseptin että sen tuottaman markkinatiedon arvon yritykselle. Konseptimallia on kuitenkin arvioitava ja kehitettävä säännöllisesti sekä käyttäjien antamien parannusehdotusten että liiketoimintaympäristön muutosten asettamien uusien vaatimusten mukaisesti. Kehitettyä konseptimallia voidaan jossain määrin hyödyntää myös muissa vientiyrityksissä. On kuitenkin huomioitava, että konseptimalli ei sellaisenaan ole käyttökelpoinen tai jäljennettävissä, sillä yritykset eroavat toisistaan niin organisaatiorakenteen, prosessien, toimintaympäristön, tietojärjestelmäarkkitehtuurin kuin arvojen ja yrityskulttuurinkin osalta.
Keywords: fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|; Digitaalinen liiketoiminnan kehittäminen